2015
DOI: 10.2507/ijsimm14(1)co2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Conflict Contagion in Customer Collaborative Product Innovation

Abstract: Customer collaborative product innovation (CCPI) is a novel pattern of new product development (NPD) to integrate customers and their knowledge as the main innovative agents and resources. In CCPI, conflict is an intrinsic and inevitable phenomenon. Conflict contagion, however, is a neglected but crucial issue for the CCPI conflict management. In order to study the mechanism and process of CCPI conflict contagion, this paper uses the idea of SIS epidemic propagation as reference, and develops a Conflict-SIS (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Su et al . (2015) have presented customer collaborative product innovation (CCPI) as a novel pattern of new product development to integrate customers and their knowledge as the main innovative agents and resources. Because conflict is an intrinsic and inevitable phenomenon in this process, they have simulated the process of CCPI conflict contagion and verified the influence of different factors on the conflict-spreading trend.…”
Section: Literature Review/background and Related Workmentioning
confidence: 99%
“…Su et al . (2015) have presented customer collaborative product innovation (CCPI) as a novel pattern of new product development to integrate customers and their knowledge as the main innovative agents and resources. Because conflict is an intrinsic and inevitable phenomenon in this process, they have simulated the process of CCPI conflict contagion and verified the influence of different factors on the conflict-spreading trend.…”
Section: Literature Review/background and Related Workmentioning
confidence: 99%
“…We considered the incentive provided to the retailer or the third-service provider by the manufacturer. We assumed that the value of µ does not rely on the quality of the product as in Guide [35] but is affected by the buy-back price [23,36]. We concluded that ∆ − (1 + µ)r j > 0 because the net per-return residual value to the manufacturer must be above zero.…”
Section: Problem Description and The Illustration Of The Symbolsmentioning
confidence: 99%
“…Su et al have presented customer collaborative product innovation (CCPI) as a novel pattern of new product development to integrate customers and their knowledge as the main innovative agents and resources. Because conflict is an intrinsic and inevitable phenomenon in this process, they have simulated the process of CCPI conflict contagion and verified the influence of different factors on the conflict-spreading trend (Su et al, 2015).…”
Section: Innovation Managementmentioning
confidence: 99%